KEADAAN PETANI JAGUNG PADA MASA PANDEMI COVID-19 DI DESA TOLOMBUKAN SATU KECAMATAN PASAN KABUPATEN MINAHASA TENGGARA (STUDI KASUS KELOMPOK TANI NAFIRI JAYA) - Jesica Almi Filisia Ratulangi; Elsje Pauline Manginsela; Martha Marejke Sendow (AGRI-SOSIOEKONOMI, 2021)
This study aims to determine the corn farming situation in the Nafiri Jaya farmer group regarding land area, capital, seeds, fertilizer, labor, and income of corn farmers during the Covid-19 pandemic in the village. Tolombukan Satu, Pasan Sub-District, Southeast Minahasa Regency. This research was conducted for 3 months from November 2020 – February 2021. The data used were primary data and secondary data. Primary data collection through interviewed with questionnaires to 10 corn farmers as respondents. Secondary data obtained from related agencies. They are village office, Pasan sub-district office, internet, books and journal articles. Data analysis carried out in this research is descriptive analysis in the form of tables, diagrams and descriptive. The results showed that the condition of corn farmers during the COVID-19 pandemic decreased concerning the size of the area to plant corn, the amount of capital used for production, the number of corn seeds, the amount of fertilizer, the number of workers working in the corn farmland, and corn farmer income.*eprm*